The Effect of Katuk Leaf (Sauropus androgynus) on Increased Milk Production in Breastfeeding Mothers - Nurhayati, Nurhayati; Rompegading, Andi Badli; Nuramalia Rahma, Besse Nuramalia Rahma; Yanti, Reski (Hayyan Journal, 2024)
Babies need breast milk (mother's milk) mother's milk). Sufficient breast milk is essential for the development of the baby. Consumption of consumption of foods such as katuk leaves is very good for increasing breast milk. Literature review on the benefits of katuk leaves for increasing breast milk production was conducted in this this study. This review was based on a systematic search study on PICO database in 9 research journals: Integrated Health Journal, Naska Poltekkes Kemenkes Semarang publication, Majority Journal, and Saintika Journal. Results The results showed that alkaloids and sterols contained in katuk leaf can increase breast milk production in breastfeeding mothers. Nine articles found through Google search, Researchgate, and Pubmed/Medline showed that any preparation of katuk leaves can increase breast milk production to meet the the needs of breastfeeding mothers. The Health Office of the Republic of Indonesia recommends this intervention as it has been proven effective. Wealthy Indonesians who are already accustomed to consuming jamu will also not hesitate to try it.